Advancements in Natural Language Processing: Towards Human-Like Understanding and Generation of Text by AI - Hussein Najm Abd Ali (BIOS: Jurnal Informatika dan Sains, 2024)
Constant advances in Natural Language Processing (NLP) have made reflected data systems sorted out for appreciating and making like individuals. This article examines the way taken by these new developments, focusing in on epic levels of progress, approaches, and weights. This article figures out the advances in standard language managing (NLP) by taking a gander at the change from rule-based systems to basic learning structures and the enhancements in semantic creation and understanding. It other than mindfully takes a gander at the moral outcomes and expected uses of reproduced data driven text age and understanding. Man-made intellectual ability (replicated data) has made massive strides in standard language managing (NLP), moving from direct rule-based plans to complex basic learning models. All things considered, NLP is ending up being closer to human-like text age and understanding. This paper deftly takes a gander at the jumbled history of NLP developments, revealing key structures, upgrades, and exploring issues. The way towards human-like text age and care is poverty stricken down, starting with rule-set up structures and going in regards to through quantifiable normal language managing and immense learning models. Similarly, the ethical points of view and social eventual outcomes of PC based data driven text age and understanding are dissected, uncovering data into the requirement for solid execution and moving focus on in this rapidly making subject.